2018
DOI: 10.3390/pharmaceutics10030099
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake Behaviors of Rigidity-Tunable Dendrimers

Abstract: Understanding of the interaction between cells and nanoparticles (NPs) is critical. Despite numerous attempts to understand the effect of several parameters of NPs on their cellular uptake behaviors, such as size, shape, surface chemistry, etc., limited information is available regarding NP rigidity. Herein, we investigate the effect of rigidity on cellular uptake behaviors of NPs, using generation 5 poly(amidoamine) dendrimer as a model. By harnessing the abundant inner cavity, their rigidity could be effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“… 26 Liu and colleagues previously studied the role of nanoparticle rigidity on cellular uptake using G5 dendrimers as soft nanoparticles and dendrimers-coated gold nanoparticles as rigid nanoparticle models. 27 They found that the uptake of dendrimer-coated gold nanoparticles was 3.2-fold higher than that observed from dendrimers in both U87MG cancer cells and L929 healthy cells. As the adsorption and cellular uptake of nanoparticles depend on their shape, surface modifications, size and charge, the enhanced cellular uptake of the gold conjugates could also be due to the cationic polymer modification on the gold nanocages and the positive charge of gold complexes.…”
Section: Discussionmentioning
confidence: 97%
“… 26 Liu and colleagues previously studied the role of nanoparticle rigidity on cellular uptake using G5 dendrimers as soft nanoparticles and dendrimers-coated gold nanoparticles as rigid nanoparticle models. 27 They found that the uptake of dendrimer-coated gold nanoparticles was 3.2-fold higher than that observed from dendrimers in both U87MG cancer cells and L929 healthy cells. As the adsorption and cellular uptake of nanoparticles depend on their shape, surface modifications, size and charge, the enhanced cellular uptake of the gold conjugates could also be due to the cationic polymer modification on the gold nanocages and the positive charge of gold complexes.…”
Section: Discussionmentioning
confidence: 97%
“…PAMAM dendrimers, which were the first commercial dendrimers with structures resembling those of proteins, had distinct dendritic structures and three-dimensional spherical shapes. PAMAM dendrimers have been employed extensively in the field of biomedical nanotechnology because of their excellent water solubility, monodispersity, tuneable molecular size, non-immunogenicity, capacity to traverse biological barriers, and ease of functionalisation [ 99 , 100 , 101 ]. PAMAM zero generation (G0) dendrimers were investigated as nanocarriers for drug administration, and conjugated G0 PAMAM dendrimers incorporated with a zinc phthalocyanine (ZnPc) photosensitiser were investigated for their effects on the sick and healthy tissues removed from human carotid arteries.…”
Section: Nanoparticles For Diagnosis and Treatment Of Atherosclerosismentioning
confidence: 99%
“… 5 , 6 For example, the particle shape has been reported to affect the intracellular uptake of the NPs and their biodistribution. 7 Additionally, the particle size 8 , 9 and the particle rigidity 10 , 11 play important roles. Active targeting, which employs ligands with a specific affinity towards the target site, has long been regarded as the optimum strategy for maximizing the tumor accumulation of NPs.…”
Section: Introductionmentioning
confidence: 99%